A CIVILIZAÇÃO DA AMAZÔNIA ALEXANDRE RODRIGUES FERREIRA E O DIRETÓRIO DOS ÍNDIOS: A EDUCAÇÃO DE INDÍGENAS E LUSO-BRASILEIROS PELA ÓTICA DO TRABALHO (Revista de História Regional, 2007)
This works subject matter is the Portugueses colonial legislation to civilize Amazonian Indians in the eighteenth century The Diretório dos Índios. This paper focuses on Alexandre Rodrigues Ferreiras criticism about it, which allows an interpretation of the law as an effort to introduce a moral labor to the Amazonian (Indian and Portuguese) people.